Análise do reflexo da qualidade de governança corporativa no processo de avaliação de empresas - Silva, Carla Carolinne dos Santos (2015)
The propose of this research was to analyze the reflection of the quality of Corporate Governance on the process of valuation in Brazilian capital market, considering the Ohlson (1995) model. Was resorted to the data of all companies that traded their shares on the BM&FBOVESPA in the period of 2010-2013. For this, a model of valuation was used, which includes a proxy variable for the quality of Corporate Governance, the Index Quality of Corporate Governance (IQGC), based on the agency theory (JENSEN; MECKLING, 1976), which dimensions were included to minimize the agency problems, which were: Composition of the Board of Directors, Ownership Structure and Control Incentive to Directors, Disclosure, Investor Protection, Audit Committee and Asymmetric Information. Among the dimensions Disclosure was the one that had the higher frequency compared to the others companies, however the Audit Committee obtained the lowest frequency. The IQGC was calculated by Principal Component Analysis (PCA), which consists in a weighted average of the principal generated components with the weights given by their respective variances. The analysis on the IQGC behavior, over the analysis period, showed a growth trend in the level of quality of corporate governance on the companies. To assess the relevance of IQGC in the process of valuation has been included in this proxy model residual income valuation (RIV) of Ohlson (1995), business valuation model based on financial variables that allow the inclusion of 'other information' that may represent factors that are important for the valuation, but that have not been reflected by the variables used. The analysis results of the data in balanced panel model also shows that the quality of corporate governance is value relevant in the Brazilian capital market, once that the model had his coefficient of determination increased with the entry of this variable, which was confirmed by the Wald test. In addition to, the intrinsic characteristics of the companies sought to investigate whether the results persist when analyzed: Size and Liquidity. The results revealed that the only evidence remain on medium size companies and among those with lower liquidity, which can be associated to the specific characteristics of Brazilian market. Given the evidence, we can not reject the hypothesis that the quality of Corporate is value relevant for the valuation in the Brazilian capital market. The result of this study are limited to the sample and the period analyzed.